The Effect of Working Capital Turnover on Profitability: Empirical Study of Textile and Garment Companies Listed on The Indonesia Stock Exchange for the 2014-2018 Period - Devita Sari; Ignatius Oki Dewa Brata (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2020)
Cash flow from operating activities is the amount of cash flow originating from working capital is the right or part owned by the owner of the company indicated in the postal capital (share capital), surplus and retained earnings (S. Munawir, 2010: 19). Profitability is a ratio to assess a company's ability to find profits or profits in a certain period. This ratio can also provide a measure of the level of effectiveness of company management which can be shown from the profits obtained from sales or from investment income (Kasmir, 2015: 22). In this study the authors use quantitative methods, with descriptive research approaches and verification analysis. by using the research method will be known a significant effect between the variables studied so that conclusions that will clarify the picture of the object under study, the sample in this study were 14 companies The analytical tool used in this study uses simple linear regression. Based on the research results, the profitability represented by ROA is influenced by the working capital turnover. Working Capital Turnover does not have a significant effect on Return of Assets.